Durability evaluation and life prediction of fiber concrete with fly ash based on entropy weight method and grey theory. (11th April 2022) - Qin, Yuan; Guan, Ke; Kou, Jialiang; Ma, Yingbiao; Zhou, Heng; Zhang, Xianwei
Highlights: The quality and strength changes in fiber concrete with fly are analyzed. The comprehensive evaluation index of fiber concrete with fly ash durability is established. GM model is used to predict the change in fiber concrete with fly ash durability value. Abstract: High amounts of sulfates are found in the soil of Nazixia area in Qinghai Province, China. As such, the sulfate attack must be considered for the construction of dams. In this paper, fiber concrete specimens with fly ash content of 0, 10%, 20%, and 30% are designed and manufactured (All the fiber contents of specimen is 0.9%), and two groups of sulfate dry–wet cycle tests were carried out (Group 1: 0 fly ash content in 2%, 5%, and 10% sodium sulfate solution dry–wet cycle; Group 2: 0, 10%, 20%, and 30% fly ash content in 5% sodium sulfate solution dry–wet cycle). We analyzed the mass, compressive strength, and split strength of specimens. Based on entropy weight method, we determined the weight of mass, compressive strength, and split strength and proposed a new comprehensive durability evaluation method that took durability value as an evaluation object. Based on the above method, GM(1, 1) model was used to simulate the change rule of durability value and predict the change rule of concrete durability under different conditions.